2016
DOI: 10.1007/s10103-016-2129-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of shorter pulse duration in cochlear neural activation with an 810-nm near-infrared laser

Abstract: Optical neural stimulation in the cochlea has been presented as an alternative technique to the electrical stimulation due to its potential in spatially selectivity enhancement. So far, few studies have selected the near-infrared (NIR) laser in cochlear neural stimulation and limited optical parameter space has been examined. This paper focused on investigating the optical parameter effect on NIR stimulation of auditory neurons, especially under shorter pulse durations. The spiral ganglion neurons in the cochl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Previous reports showed that PBM is able to influence the intracellular calcium levels , consistent with the fundamental role of this ion in nociception . We assessed calcium flow in DRG neurons after PBM following cell exposure to capsaicin, as a physiological stimulus.…”
Section: Resultsmentioning
confidence: 58%
“…Previous reports showed that PBM is able to influence the intracellular calcium levels , consistent with the fundamental role of this ion in nociception . We assessed calcium flow in DRG neurons after PBM following cell exposure to capsaicin, as a physiological stimulus.…”
Section: Resultsmentioning
confidence: 58%
“…Short pulses of infrared light delivered from a focused source (i.e., laser) can be used to activate target neural tissue [97]. The applicability of this idea to cochlear and retinal implants is being actively investigated, with promising initial results from in vitro and in vivo experiments in animal models [98][99][100]. Optogenetics is another alternative, involving transgenic manipulations to introduce photosensitive ion channels (e.g., channelrhodopsin-2, ChR2) into neurons so that their activation can be directly controlled by specific light stimulation [101].…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Although the absorption coefficient of near-infrared light is smaller than that of mid-infrared light, it can still activate neural tissue. Wang et al (2017) successfully induced auditory brainstem responses in deaf guinea pigs by stimulating their auditory neurons with 810 nm nINS. Yoo et al (2013) reported that using 20-40 mW and 808 nm nINS could induce neuronal behavior changes in the deep brain of rats.…”
Section: Introductionmentioning
confidence: 99%